Learning Processes on Portuguese for Speakers of Other Languages: the case of Adult Immigrants with Little or no Literacy in any Language - Matias, A.R.; Ortiz, Alejandra; Oliveira, Nuno (II Simpósium International EDiSo - Discursos e Sociedades em Movimento, 2015)
Programmes of Portuguese for Speakers of Other Languages are recent in Portugal, and in general aim to promote labour market integration, access to the Portuguese Nationality, and cognitive valorization. These are Portugal Acolhe (PA, 2001); Português para Todos (PPT, 2007); and, more indirectly, Competências Básicas (CB, 2010, originally aimed for national citizens). However, such measures are not adapted to adult immigrants with few or no literacy in any language, even if they represent about 10% of total trainees since 2001 (PA, PPT). Even though, the latter do attend these programmes due to lack of offer, but hardly succeed in adapting to its aims in terms of social, educational and symbolic capacities. Knowing that learning modalities impact significantly in learners’ motivation and learning -- with significant intergenerational impact -- and the studies focusing on this population specific needs are almost inexistent, this paper aims to contribute for their understanding. For this purpose, we present the first results of a sociological study on the participation of immigrant adults with few or no literacy in any language within the aforementioned programmes, and discuss the institutional recognition of this population, so far neglected. We focus on the institutional recognition of this population needs, within three angles: as a linguistic consequence of the migration phenomenon; from the perspective of adults’ education; for the importance on the implicit intergenerational impact.